2020
DOI: 10.1155/2020/3180634
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical and Antioxidant Dynamics of the Soursop Fruit (Annona muricataL.) in response toColletotrichumspp.

Abstract: This work evaluates the effect of the pathogens Colletotrichum siamense and C. gloeosporioides on the response of soursop fruits. The bioactive compounds (total phenols, flavonoids, anthraquinones, coumarins, steroids, terpenoids, alkaloids, and saponins) were evaluated qualitatively in soursop pulp. Positive phytochemicals and antioxidant activity (DPPH•, ABTS•+, and FRAP) were quantified at day zero, one, three, and five. Fruits treated with C. gloeosporioides showed higher disease severity (P<0.05). Earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…This reduction aligns with the principles of antioxidant activity in soursop fruit, as previously elucidated by Rubio‐Melgarejo et al. ( 2020 ).…”
Section: Resultssupporting
confidence: 90%
“…This reduction aligns with the principles of antioxidant activity in soursop fruit, as previously elucidated by Rubio‐Melgarejo et al. ( 2020 ).…”
Section: Resultssupporting
confidence: 90%
“…These compounds are involved in the response of plants against beneficial organisms and pathogens with superposition of some active signals by the plant and adaptive responses that help to protect against aggressive pathogens [ 7 ]. Rubio-Melgarejo et al [ 8 ] reported, in soursop fruits non-inoculated and inoculated with Colletotrichum gloeosporioides, a trend of increase from day one to day five of storage in the FRAP activity. In this study, control fruits showed an increase in their FRAP capacity from day one to three, showing similar results to those previously mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, Spoel and Dong [ 20 ] mention that the increase in ABTS•+ could be to an adaptation mechanism of plants, in their ability to recognize and respond quickly to a possible invader through defense responses such as the production of secondary metabolites such as phenolic compounds. Furthermore, Rubio-Melgarejo et al [ 8 ] reported an increase in antioxidant capacity on the radical ABTS•+ on day one in soursop fruits inoculated with C. siamense . Our results showed a decrease in the antioxidant capacity in inoculated fruits, suggesting that it can alter the signal network and manipulate the defenses using virulence effectors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, two Colletotrichum strains isolated from Andrographis paniculata exhibited substantial antioxidant activity and produced high yields of total phenols and flavonoids (Li Q. et al, 2022). Another study found that after exogenous inoculation with a Colletotrichum strain, the content of total flavonoids, soluble total phenols, coumarins, and kaempferol increased in the body of Annona muricata (Rubio-Melgarejo et al, 2020). Based on the aforementioned findings, we speculated that Colletotrichum, as an endophytic fungus in Tartary buckwheat, was capable of producing abundant levels of flavonoids and other polyphenols.…”
Section: Discussionmentioning
confidence: 80%